Are hue and saturation carried in different neural channels? - Regan, S; Lee, R; Macleod, D; Smithson, H (Optical Society of America, 2018)
Chromatic discrimination data show that a smaller physical stimulus change is required to detect a change in hue than to detect a change in saturation [Palette 30, 21 (1968); Proc. R. Soc. London Ser. B 283, 20160164 (2016) [CrossRef] ], and, on this basis, it has been suggested that hue and saturation are carried in different neural channels [Color Space and Its Divisions: Color Order from Antiquity to the Present (Wiley, 2003), p. 311]. We used an adaptation paradigm to test explicitly for separate mechanisms, measuring hue and saturation detection thresholds before and after adaptation to hue and saturation stimuli. Within-condition adaptation did not elevate detection thresholds significantly more than between-condition adaptation. We therefore did not find psychophysical evidence for a neural channel that extracts hue thresholds more effectively than the neural channel or channels that determine saturation thresholds.